Demands of professional female cycling races: Influence race level and race duration (single or multi-day events) - van Erp, T.; Lamberts, R. P. (European Journal of Sport Science, 2022)
This study is governed by two aims: firstly, expanding the meagre knowledge store regarding the demands set by professional female road cycling and, secondly, ascertaining whether these demands vary in relation to different race-levels and race duration (single- or multi-day events). A total of 1349 female professional road races was analysed and demands (intensity, load and performance) were determined. Races were classified based on race level (i.e. Women's World Tour [WWT], level.1 and level.2 according to the International Cycling Federation) and race duration (single- or multi-day events). Differences were assessed with a multilevel random intercept model whilst the strength of said differences were indicated by Cohen`s d (0-0.19 trivial; 0.20-0.59 small; 0.60-1.1.9 moderate; 1.20-1.99 large; =2.00 very large). In general, no moderate differences for load and intensity were noted for the different race levels. This result contrasts with data obtained from male road cycling. Moderate higher 3 and 5 min maximal mean power (MMP) values were noted in the WWT compared to Level.2 races. More substantial differences were found to exist between single- and multi-day races with single-day races presenting small to large higher load and intensity values. In addition, single-day races presented higher MMPs overall durations (5 s-60 min) although these differences can be rated trivial to small. This study contributes to the limited knowledge store describing demands in professional female cycling. The reported data provide valuable insights which may aid practitioners and/or coaches in preparing female professional cyclists for races.